Integrating grazing intensity regulation and livestock mobility restoration: A practical test for China’s next-generation rangeland policies - Jianguo Xue; Zunlan Luo; Zhang Chen; Ping Ge; Junchen Lv; Jianhui Huang; Ang Li (Agriculture, Ecosystems & Environment, 2026)

A pH-responsive, kojic acid-based amphiphilic polymer as a nanocarrier for targeted herbicide delivery - Yuying Xie; Yangchun Ge; Zhuochao Shen; Yupeng Qiu; Haohua Zhang; Changmeng Sun; Jiangkuan Tang; Bingke Li; Junran Xu; Ping Liang; Yubang Tao; Shengtian Wang; et al. (Crop Protection, 2026)

Bipyridine-based covalent organic framework for trace-level nanofluidic detection of chlorobenzoquinone - Xu-Qin Ran; Xin-Ge Cai; Xiao-Jiao Ren; Xiu-Ping Yan; Hai-Long Qian (Chemical Engineering Journal, 2026)

Disruption of progesterone synthesis by PBDEs: Potent inhibition of human and rat placental 3β-hydroxysteroid dehydrogenase by the metabolite 4-Bromodiphenyl ether - Lubin Xie; Qianjin Fei; Ming Su; Yunbing Tang; Yang Zhu; Ren-shan Ge; Ping Duan; Chengshuang Pan (Toxicology and Applied Pharmacology, 2026)

CvbZIP81 contributes to selenium accumulation by regulating sulfate transports in Cardamine violifolia - Luxin Feng; Jiarui Zheng; Sirui Zeng; Ge Li; Sisi Wang; Ping Yun; Zexiong Chen; Renhua Huang; Qiangwen Chen; Sergey Shabala; Feng Xu (Plant Science, 2026)

Hydrometeorological thresholds controlling soil carbon, nitrogen, and vegetation productivity dynamics in an Inner Mongolian grassland watershed (1981–2019) - Ge Gao; Jia Liu; Limin Duan; Yixuan Wang; Yicheng Wang; Jianzhu Li; Ping Feng; Josep Peñuelas (CATENA, 2026)

Study on Reinforcement and Deformation Control of Soft Soil Foundation for Shield Tunnel Crossing the Shanghai-Nanjing Railway - Ya Lu; Ping Yang; Shuqiang Feng; Yufei Ge; Ting Zhang (Transportation Geotechnics, 2026)

BrAKT1 overexpression enhances clubroot susceptibility through dysregulation of host physiological processes in pak choi - Samiah Arif; Yǔmeng Yan; Yufan Ge; Muhammad Sanaullah Malik; Ping Li; Saeed ur Rahman; Yidong Zhang (Physiological and Molecular Plant Pathology, 2026)

Retraction notice to ‘Association between prenatal exposure to ambient particulate matter and risk of hypospadias in offspring: A systematic review and meta-analysis’ [Environ. Res. 192 (2021) 110190] - Hua-Chuan Lin; Jing-Min Guo; Pin Ge; Ping Ou (Environmental Research, 2026)

A Sea Surface Salinity error correction model integrating physical models and complex environmental influences - Yanling Han; Wenbin Zhao; Qinqin Sun; Ge Song; Ping Ma; Yun Zhang; Chuanxiang Hua; Shouqi Cao (International Journal of Remote Sensing, 2026)

Corrigendum to“Functional characterization of odorant binding proteins involved in detection of host plant volatiles from the moringa pest Noorda blitealis” [Insect Biochem. Mol. Biol. 192 (2026) 104578] - Yunkang Ge; Zubing Zhang; Ping Gao; Wenkai Liang; Jiming Long; Jiaying Zhu (Insect Biochemistry and Molecular Biology, 2026)

Unraveling the critical role of ClO• in the degradation of emerging organic contaminants by far-UVC/chlorine: Radical contribution assessment and influence of water matrix - Ping Li; Ge Zeng; Wenjun Zhang; Qiuling Lu; Haonan Lu; Kai Wang; Jun Ma; Yan Zhang; Tao Yang (Chemical Engineering Journal, 2026)

Simulations of summer ENSO events with different evolutions of equatorial Pacific SSTAs in CMIP6 models - Shuhao Ge; Ping Huang; Xianke Yang (Atmospheric Research, 2026)

Functional characterization of odorant binding proteins involved in detection of host plant volatiles from the moringa pest Noorda blitealis - Yunkang Ge; Zubing Zhang; Ping Gao; Wenkai Liang; Jiming Long; Jiaying Zhu (Insect Biochemistry and Molecular Biology, 2026)

Lewis acid-mediated choline chloride-glycerol deep eutectic solvent pretreatment for Goji berry branches: Enhancing enzymatic saccharification and high-value utilization of lignin - Bingxue Sun; Huaitao Jiang; Guan-Ping Jin; Shi-Kui Han; Bolin Liu; Xiaoli Ge; Xiaoyou Xiu; Biaode Yang (Biomass and Bioenergy, 2026)

A label-free fluorescent/electrochemical dual-mode zinc complex biosensor for highly selective and sensitive detection of tetracycline - Zhi-Lin Mu; Zeyu Zhu; Jiale Cheng; Xingyu Zhan; Chen He; Zhongyan Chen; Hong-Ping Xiao; Jing-Yuan Ge (Analytica Chimica Acta, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

A Novel Wave-Absorbing Support System for Mitigating Rock Burst in Deep-Buried Hard Rock Tunnels - Yue-Mao Zhao; Zheng-Chen Ge; Ben-Guo He; Cheng-Xiang Yang; Xing-Long Li; Xiao-Jun Yu; De-Xian Li; Yong-Ping Liu (Rock Mechanics and Rock Engineering, 2026)

Chemically modified bacterial cellulose–mediated fiber salting-out method for preparing tough hydrogels - Bei Zhang; Xin-Xin Chen; Xiao-Rui Ge; Xin-Ping Wang; Xiao-Hui Yao; Wei-Guo Zhao; Tao Chen; Dong-Yang Zhang (Carbohydrate Polymers, 2026)

Improved U-Net with enhanced spatiotemporal features for Chlorophyll-A concentration prediction in the Zhoushan fishery - Yanling Han; Yizhuo Cai; Ping Ma; Ge Song; Jing Wang; Yun Zhang; Shuhu Yang; Zhonghua Hong (Remote Sensing Applications: Society and Environment, 2026)

Numerical prediction on cavitation characteristics of a marine propeller in oblique flow without and with hull wake effects - Yu Sun; Shengyao Ge; Rui Wu; Wenyu Chen; Han Han; Depeng Ma; Huan Ping (Ocean Engineering, 2026)

Seasonal dynamics of aqueous phase from hydrothermal carbonization of waste activated sludge: Unraveling composition, ecological risks, and resource opportunities - Tingting Yang; Ninghui Song; Xue Zhang; Yanqi Shi; Ping Li; Mingzhu Zhang; Feng Ge (Journal of Cleaner Production, 2026)

Synergistic promotion of diabetic wound healing by glucose-responsive functional chitosan-based composite nanohydrogels - Runze Yang; Jiale Sun; Guanglan Peng; Mingcai Wu; Chengen Guan; Jianping Yang; Zeyuan Wang; Wanzhen Li; Longbao Zhu; Jun Wang; Zuchun Zhao; WeiWei Zhang; et al. (Carbohydrate Polymers, 2026)

Comparison and mechanism of understory drought resistance under typical tree species with long-term restoration duration (over 30 years) on the Loess Plateau - Zixin Zhan; Tianjiao Feng; Libo Ge; Xuemei Mei; Ping Wang (European Journal of Forest Research, 2026)

Effects of Continuous High Temperature Stress on Growth and Physiological Metabolism in Thermosensitive and Heat-Tolerant Passion Fruit Cultivars - Hai-bin Luo; Jie Gui; Cheng-Mei Huang; Yong-cai Huang; Ge Chen; Hui-Qing Cao; Ping Jiang; Liu Yang (Tropical Plant Biology, 2026)

MTA-SM: Multi-machine path planning and time-window scheduling joint optimization method in hilly safflower harvesting - Liwei Yang; Ping Li; Zhongshuo Ding; Chao Sun; Fei Chen; Yijiang Zheng; Yun Ge (Computers and Electronics in Agriculture, 2026)

Fate and risk of pesticides in drinking water: From source to tap using a comprehensive analysis and prioritization approach - Tingting Yang; Feng Ge; Yuan Hong; Yixuan Wang; Gang Zhou; Huimin Chen; Ninghui Song; Ping Li (Journal of Environmental Sciences, 2026)

Dipole-engineered pyridinium iodide passivation for efficient Sn-Pb and all-perovskite tandem solar cells - Ciyu Ge; Chenwei Ni; Qi Xu; Bokai Hao; Wei Ai; Chengjie Deng; Peiyan Zhang; Xinzhi Zu; Hongyan Lu; Zeyu Zhang; Weijun Ke; Haisheng Song; et al. (Chemical Engineering Journal, 2026)

Comprehensive genomic analysis of the maize ACP gene family reveals ZmACP1-mediated salt stress tolerance in Arabidopsis - Yunhao Wu; Junyu Chen; Hanqiu Ge; Xing Rong; Yuchen Wang; Meiwang Zhang; Zhigang Li; Yingrui Xi; Junfeng Tang; Junyi Li; Ping Li; Baohua Wang; et al. (Plant Cell Reports, 2026)

Isolation and identification of Desmodesmus sp. HDMA-07: Nutrient removal and biodiesel production potential in flax fiber wastewater - Han Wang; Xinyi Wang; Boqi Wang; Yimeng Lin; Jingping Ge; Wenxiang Ping (Process Safety and Environmental Protection, 2026)

New Pachyportax fossils from the Late Miocene Shuitangba locality, Yunnan, revealing the early Bovini evolution and radiation - Ding-Ge Guo; Sayyed Ghyour Abbas; Qi-Gao Jiangzuo; Chun-Xiao Li; Yan-Wu Yang; Jia-Yong Cao; Bin Zou; Shi-Qi Wang; Xue-Ping Ji (Palaeoworld, 2026)

Synergistic effect of flow field and porous transport layer matching on mass transfer and early-stage degradation mitigation in PEMWE under high operating current densities - Xiao Ge; Guanlei Zhao; Yu Xiao; Jiaxi Liu; Jingjian Chen; Ping He; Manhong Huang; Jinli Qiao (Fuel, 2026)

Mechanistic insight into curcumin-induced conjugative plasmid transfer acceleration: Role of intracellular arginine uptake - Min-ge Wang; Kai-di Liu; Wen-jie Jin; Run-bo Li; Jun-qi Liu; Liang-xing Fang; Jian Sun; Xiao-ping Liao (Food Microbiology, 2026)

Corrigendum to “Dendrobium officinale polysaccharide promotes M1 polarization of TAMs to inhibit tumor growth by targeting TLR2” [Carbohydrate Polymers 292 (2022) 119683] - Hong-Yan Wang; Ji-Chun Ge; Feng-Yun Zhang; Xue-Qiang Zha; Jian Liu; Qiang-Ming Li; Jian-Ping Luo (Carbohydrate Polymers, 2026)

Synergistic photothermal-magnetic nanoplatform: Recyclable TEG-SPIONs for ultra-efficient pathogen elimination in medical wastewater - Fei Ge; Yimei Wang; Jun Ge; Guoqiang Yang; Xinxin Liu; Shuxian Hou; Xuechao Shi; Yao Xiao; Shujie Li; Weiwei Zhang; Wanzhen Li; Ping Song; et al. (Journal of Environmental Chemical Engineering, 2025)

Genome-wide survey and expression analysis of JAZ genes in watermelon (Citrullus lanatus) - Yan-Ge Li; Jing Zhang; Xiu-Xiu Cai; Le-Ping Fan; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Molecular Biology Reports, 2025)

VOC emissions characteristics and cooperative control by combustion adjustment and APCDs in supercritical coal-fired power plants - Penghui Ge; Jie Wu; Longchun Zhong; Wei-Ping Pan (Journal of Hazardous Materials, 2025)

Bench- and pilot-scale degradation of organic pollutants in high-salt wastewater using air microbubble discharge plasma jet - Jian-Ping Liang; Da-Wei Ge; Ke Lu; Hao Yuan; Chao-Jun Chen; Zi-Kai Zhou; De-Zheng Yang (Desalination, 2025)

Microenvironment modulation of metal-organic frameworks for catalytic hydrogenation reaction - Yifan Zhang; Tao Ban; Juan Chen; Hongyi Gao; Jingjing Wang; Jitti Kasemchainan; Ping Yang; Ge Wang (Chemical Engineering Journal, 2025)

A source-to-sink multiproxy analysis of late Eocene regional drainage evolution in the Beibuwan Basin of the South China Sea - Mingxuan Tan; Lianpu Sun; Mianpei Chen; Jiawang Ge; Ping Wang; Peigang Ren (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Gaseous ozone assisted Maillard reaction of chickpea protein isolate- arabinose: Improving structural and functional properties and enhancing emulsion stability - Xiaopeng Wei; Ziyan Zhou; Xiaoyuan Wang; Megan Povey; Guo Liu; Shanshan Zhang; Ping Geng; Lihua Zhang; Zhenzhen Ge (Innovative Food Science & Emerging Technologies, 2025)

Application potential of submicron-sized bamboo cellulose as natural Pickering emulsion stabilizers: Structural properties and stabilization mechanisms - Chen-long Hou; Hao-tian Wei; Chang Liu; Hui-min Yang; Li-Chun Chen; Jian-ping Xu; Lu-yao Wang; Xiu-hua Rao; Jian-jun Huang; Qing Ge (Food Chemistry, 2025)

Daily asian-pacific oscillation and associated rainfall anomalies in Central-Northern China and precursory atmospheric signals - Rongwei Liao; Ping Zhao; Ge Liu (Atmospheric Research, 2025)

Isomer-specific ecotoxicity and occurrence of ibuprofen: Underestimated risks in aquatic ecosystems - Ping Ge; Na Liu; Yeyao Wang; John.P. Giesy; Xiaowei Jin (Journal of Hazardous Materials, 2025)

Occurrence, molecular transformation and prioritizing environmental risks of organic nitrogen in aqueous phase from hydrothermal carbonization of waste activated sludge - Tingting Yang; Lichao Tan; Jiaqi Ge; Xue Zhang; Gang Zhou; Ping Li; Ninghui Song; Feng Ge (Journal of Hazardous Materials, 2025)

Cascade regulatory mechanism of soil organic phosphorus mineralization mediated by quorum sensing signal molecules C4/C6/C8-HSL: Dynamic response based on phosphatase secretion of core species - Zhenchao Wu; Jie Kang; Liangyang Mao; Yueyi Liu; Shuo Li; Weige Yao; Ying Yang; Xiujun Tu; Yuhao Guo; Jinyu Du; Xuan Tang; Tong Yang; et al. (Chemical Engineering Journal, 2025)

Identification and characterization of the miR396f-GRF10 module in phase transition of Lilium - Meiqi Song; Ping Lu; Yue Yin; Xuewei Zhang; Wei Ge; Kezhong Zhang (Planta, 2025)

Transcriptome-Wide Sequencing Identifies Non-Coding RNAs and Their Competing Endogenous RNA Networks During the Stages of pPGCLCs-Induced Differentiation - Zhan-Zhong Qiao; Qiu-Yuan Pang; Chang Xu; Xin-Lei Feng; Ming-Xin Zang; Ping Wang; Ying Zhang; Yong-Chao Liu; Qian-Ru Han; Wei Shen; Wei Ge; Shun-Feng Cheng (Stem Cell Reviews and Reports, 2025)

In vivo and in vitro degradation and biological toxicity studies of polyesters with varying degradation rates - Ze-Yang Zhang; Wei-Zhen Zheng; Zhi-Chao Zhen; Xiao Li; Ping-Li Wang; Bo Lu; Xiu-bin Yang; Dan Huang; Jun-Hui Ji; Ge-Xia Wang (Journal of Hazardous Materials, 2025)

AMF and biochar reshape the bacterial network in rhizosphere soil of Ricinus communis under chromium (Cr) stress and improve soil quality - Yuqiang Wen; Ruotong Wu; Tianle Xu; Ranran Cao; Ge Song; Dandan Qi; Wei Chang; Kun Li; Yuan Ping; Mengmeng Zhang; Xiaoxu Fan; Fuqiang Song (Journal of Hazardous Materials, 2025)

Enhancing vegetable yield and quality in urban farming under soil and soil-less conditions: the synergistic role of biochar in food security and waste management - Xin Yang; Siew Cheong Wong; Li Ya Ge; Wei Ping Chan; Grzegorz Lisak (Journal of Cleaner Production, 2025)

Exploring exopolysaccharide production from sugarcane bagasse: Mechanisms and processes involving Leuconostoc mesenteroides - Yi Yang; Ziwen Wang; Zehai Chen; Yang Qiu; Dan Zhao; Renpeng Du; Jingping Ge; Wenxiang Ping (Chemical Engineering Journal, 2025)

Using quantitative evaluation model to assess the environmental benefits of metabolites in flax retting wastewater aerobic compost: The trade-offs of core species build the profiles of beneficial and harmful metabolites converted from lignocellulose - Ying Yang; Zhichao Yang; Jie Kang; Zhenchao Wu; Yangcun Sun; Xinbo Cao; Yuhao Guo; Xiujun Tu; Liangyang Mao; Shuo Li; Weige Yao; Jingping Ge; et al. (Chemical Engineering Journal, 2025)

Intensive rotational grazing has positive effects on productivity of rangeland - Ping Ge; Jianguo Xue; Yaqian Ru; Yulin Li; Dongxu Li; Peng Han; Ang Li; Jianhui Huang (Agriculture, Ecosystems & Environment, 2025)

Aged microplastics-induced growth inhibition via DNA damage, GH/IGF-1 and HPT axes disruption in zebrafish larvae - Qing Ge; Tong Zheng; Ping Ding; Zhenyuan Li; Xihua Lin; Xintong Li; Miao He; Guocheng Hu (Science of The Total Environment, 2025)

Lanthanum-mediated enhancement of low temperature hydrogenation activity and stability in nickel catalyst supported by MOFs - Zhiyuan Liu; Yan Gao; Changan Wang; Yuanjie Zhang; Hongyi Gao; Ping Yang; Siqi Liu; Juan Chen; Zhimeng Liu; Jingjing Wang; Xinmeng Xu; Ge Wang (Chemical Engineering Journal, 2025)

Moisture–Microbial Interaction Amplifies N 2 O Emission Hot Moments Under Deepened Snow in Grasslands - Jie Luo; Yong Peng; Zhou Jia; Yuntao Wu; Yuxuan Gao; Nairsag Jalaid; Xingming Zhang; Heng Ge; Bowen Qing; Hongyi Chen; Yanxin Zhan; Ping Li; et al. (Global Change Biology, 2025)
Freeze–thaw‐induced N 2 O pulses could account for nearly half of annual N 2 O fluxes in cold climates, but their episodic nature, sensitivity to snow cover dynamics, and the challenges of cold‐season monitoring complicate their accurate estimation and representation in global models. To address these challenges, we combined in situ automated high‐frequency flux measurements with cross‐ecoregion soil core incubations to investigate the mechanisms driving freeze–thaw‐induced N 2 O emissions. We found that deepened snow significantly amplified freeze–thaw N 2 O pulses, with these ~50‐day episodes contributing over 50% of annual fluxes. Additionally, freeze–thaw‐induced N 2 O pulses exhibited significant spatial heterogeneity, ranging from 3.4 to 1184.1 μg N m −2 h −1 depending on site conditions. Despite significant spatiotemporal variation, our results indicated that 68%–86% of this variation can be explained by shifts in controlling factors: from water‐filled pore space (WFPS), which drove anaerobic conditions, to microbial constraints as snow depth increases. Below 43% WFPS, soil moisture was the overwhelmingly dominant driver of emissions; between 43% and 66% WFPS, moisture and microbial attributes (including denitrifying gene abundance, nitrogen enzyme kinetics, and microbial biomass) jointly triggered N 2 O emissions pulses; above 66% WFPS, microbial attributes, particularly nitrogen enzyme kinetics, prevailed. These findings suggested that maintaining higher soil moisture served as a trigger for activating microbial activity, particularly enhancing nitrogen cycling. Furthermore, we showed that hotspots of freeze–thaw‐induced N 2 O emissions were linked to high root production and microbial activity in cold and humid grasslands. Overall, our study highlighted the hierarchical control of WFPS and microbial processes in driving freeze–thaw‐induced N 2 O emission pulses. The easily measurable WFPS and microbial attributes predictable from plant and soil properties could forecast the magnitude and spatial distribution of N 2 O emission “hot moments” under changing climate. Integrating these hot moments, particularly the dynamics of WFPS, into process‐based models could refine N 2 O emission modeling and enhance the accuracy of global N 2 O budget prediction.

Anti-hypoxia polyacetylenes and sesquiterpenoids from Codonopsis pilosula (Franch.) Nannf - Zhuo-Yang Cheng; Jun-Ge Jin; Meng Yan; Xin-Yue Chen; Jian-Kuan Li; Jian-Ping Gao; Jiang-Tao Zhou (Natural Product Research, 2025)

Mesua ferrea L. extract inhibits cell invasion and tumor growth in breast cancer in vitro and in vivo - Zhi-Ying Liu; Ge Ge; Shuang-Shuang Ma; Xi-Ya Chen; Yue Cong; Shu-Yun Wang; Ya-Ping Guo (Tissue and Cell, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Early-stage performance degradation mechanisms of proton-exchange membrane water electrolysis under high operating current densities - Xiao Ge; Yu Xiao; Guanlei Zhao; Xi Luo; Jiaxi Liu; Jingjian Chen; Ping He; Manhong Huang; Jinli Qiao (Fuel, 2025)

Steam-assisted one-step fabrication of Ni-Ce biochar catalysts for enhanced biomass pyrolysis-steam reforming - Jiali Guo; Jit Loong Cyrus Foo; Liya Ge; Wei Ping Chan; Andrei Veksha; Guicai Liu; Zhifeng Hu; Shuai Guo; Grzegorz Lisak (Chemical Engineering Journal, 2025)

The Role of ICP Monitoring in Minimally Invasive Surgery for the Management of Intracerebral Hemorrhage - Ge Zhang; Yunjie Li; Danyang Chen; Zhuojin Wu; Chao Pan; Ping Zhang; Xingwei Zhao; Bo Tao; Han Ding; Cai Meng; Diansheng Chen; Wenjie Liu; et al. (Translational Stroke Research, 2025)
Intracerebral hemorrhage (ICH) is the second major stroke type, with high incidence, high disability rate, and high mortality. At present, there is no effective and reliable treatment for ICH. As a result, most patients have a poor prognosis. Minimally invasive surgery (MIS) is the fastest treatment method to remove hematoma, which is characterized by less trauma and easy operation. Some studies have confirmed the safety of MIS, but there are still no reports showing that it can significantly improve the functional outcome of ICH patients. Intracranial pressure (ICP) monitoring is considered to be an important part of successful treatment in traumatic brain diseases. By monitoring ICP in real time, keeping stable ICP could help patients with craniocerebral injury get a good prognosis. In the course of MIS treatment of ICH patients, keeping ICP stable may also promote patient recovery. In this review, we will take ICP monitoring as the starting point for an in-depth discussion.

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

Synergistic neurotoxicity of clothianidin and photoaged microplastics in zebrafish: Implications for neuroendocrine disruption - Ping Ding; Yajing Han; Yanan Sun; XiaoXia Chen; Qing Ge; Wei Huang; Lijuan Zhang; Adela Jing Li; Guocheng Hu; Yunjiang Yu (Environmental Pollution, 2025)

Corrigendum to “Cryopreservation of porcine skin-derived stem cells using melatonin or trehalose maintains their ability to self-renew and differentiate” [Cryobiology 107 (2022) 23–34] - Jia-Dong Sun; Yu Sun; Tian Qiao; Shu-Er Zhang; Paul W. Dyce; Yuan-Wei Geng; Ping Wang; Wei Ge; Wei Shen; Shun-Feng Cheng (Cryobiology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Species-level source tracing of psychrotrophic bacteria contamination in raw milk from large-scale farms via SMRT sequencing - Lijiao Liang; Ping Wang; Zheren Wang; Xiaomei Zhao; Qinglong Ji; Beibei Xu; Di Wu; Yiqiang Ge; Ying Chen (Food Research International, 2025)

Taste characterization and molecular docking study of novel umami flavor peptides in Yanjin black bone Chicken meat - Chaohui Yang; Xuehai Ge; Changrong Ge; Ping Zhao; Shuangmin Liang; Zhichao Xiao (Food Chemistry, 2025)

Spatial and anchoring effects of zirconia-doped 3D scaffolds for stable zinc anodes - Jinqiu Ye; Tiancheng Ge; Xin Qu; Mohamedazeem M. Mohideen; Ce Wang; Ping Hu; Yong Liu (Chemical Engineering Journal, 2025)

Isolation and characterization of high ammonium tolerant Fasciculochloris sp. HDMA-06 and its potential for nutrient removal and biodiesel production in simulated swine wastewater - Han Wang; Xinyi Wang; Jixin Liu; Yimeng Lin; Jingping Ge; Wenxiang Ping (Journal of Water Process Engineering, 2025)

Identification of suitable vegetation restoration areas and carrying capacity thresholds on the Loess Plateau - Libo Ge; Xuemei Mei; Jianhua Ping; Erfang Liu; Jiawei Xie; Jiwei Feng (Journal of Environmental Management, 2025)

Inter-annual and spatial variations of air-sea CO2 fluxes and acidification mechanism in the coastal waters of Qingdao, China during 2011–2019 - Zheng-Xin Hu; Tie Li; Tian-Tian Ge; Jing-Wen Hu; Ping-Wang; Chun-Ying Liu; Gui-Peng Yang (Marine Pollution Bulletin, 2024)

Abscisic acid treatment positively regulates suberin polyaliphatics biosynthesis at wound sites in postharvest yam tubers - Xiaopeng Wei; Jing Xue; Ping Geng; Guo Liu; Ziyan Zhou; Chuanxue Yin; Yiwen Ji; Jiajun Dai; Guanhua Tang; Guangyuan Zhao; Wei Zong; Zhenzhen Ge; et al. (Postharvest Biology and Technology, 2024)

Model the evolutionary pattern of N species and pool size in groundwater continuum by utilizing measured source and sink rates of nitrate and ammonium - Li-Li Han; Lianghao Ge; Ehui Tan; Wenbin Zou; Li Tian; Ping Li; Min Nina Xu; Shuh-Ji Kao (Journal of Hazardous Materials, 2024)

Closed-loop recycling of biodegradable poly(butylene adipate-co-terephthalate) based on hydrolysis and repolymerization strategy - Wei-Zhen Zheng; Xiao Li; Jing Xie; Ze-Yang Zhang; Ping-Li Wang; Dan Huang; Zhong-Lai Ren; Jun-Hui Ji; Ge-Xia Wang (Journal of Environmental Chemical Engineering, 2024)

Avi-tag mediated Phage@gold nanoprobe illuminates bacteria - Ping Li; Mangmang Shen; Haojie Ge; Xinan Jiao; Xin Zhou; Xiang Chen (Chemical Engineering Journal, 2024)

Unraveling MOF growth in colloids with controllable dual-doping through ultrafast sintering for wide temperature range LIBs - Bolin Zou; Semi Kim; Xingyu Zhang; Qiang Chang; Weiwei Ping; Daeun Jeong; Binghui Ge; Xingqi Liao; Zhimei Huang; Juyeong Kim; Xuyong Feng; Hongfa Xiang; et al. (Chemical Engineering Journal, 2024)

Nuclear data processing and benchmarking for the test edition of China evaluated photonuclear data library (CENDL/PD-b) - Ping Liu; Huanyu Zhang; Xiaofei Wu; Ruirui Xu; Xi Tao; Yuan Tian; Yongli Jin; Jimin Wang; Zhi Zhang; Zhigang Ge; Nengchuan Shu (Annals of Nuclear Energy, 2024)

Potassium persulfate enhances humification of chicken manure and straw composting: The perspective of rare and abundant microbial community structure and ecological interactions - Xiujun Tu; Bo Yin; Jie Kang; Zhenchao Wu; Yuhao Guo; Guoxu Ao; Yangcun Sun; Jingping Ge; Wenxiang Ping (Science of The Total Environment, 2024)

Metagenomic analysis unveiled the response of microbial community and antimicrobial resistome in natural water body to duck farm sewage - Chang Fang; Kai-di Liu; Feng-jie Tian; Jin-ying Li; Si-jie Li; Rong-min Zhang; Jian Sun; Liang-xing Fang; Hao Ren; Min-ge Wang; Xiao-ping Liao (Environmental Pollution, 2024)

Unveiling key impact parameters and mechanistic insights towards activated biochar performance for carbon dioxide reduction - Wen Qian Chen; Jit Cyrus Loong Foo; Andrei Veksha; Wei-Ping Chan; Li Ya Ge; Grzegorz Lisak (Bioresource Technology, 2024)

Attachment processes of negative flashes with multiple return strokes to a tall tower observed at close distances - Yan Gao; Mingli Chen; Zilong Qin; Zongxu Qiu; Shaoyang Wang; Ge Zhang; Qi Qi; Ya-ping Du (Atmospheric Research, 2024)

Sustainable recycling of the biodegradable polyester poly(butylene succinate) via selective catalytic hydrolysis and repolymerization - Wei-Zhen Zheng; Xiao Li; Peng-Yuan Xu; Ze-Yang Zhang; Ping-Li Wang; Bo Lu; Dan Huang; Zhi-Chao Zhen; Jun-Hui Ji; Ge-Xia Wang (Resources, Conservation and Recycling, 2024)

Sustainable utilization of mining resources: Exploring the impact of FinTech on green development from the perspective of mining enterprises - Wenfeng Ge; Ping Yang; Xu Pan; Qiying Ran (Resources Policy, 2024)

Investigate the optimum design of atomizing nozzles for coal dust suppression by using multifactor level response surface methodology - Shuaishuai Ren; Deji Jing; Shaocheng Ge; Yinuo Chen; Ping Chang (Process Safety and Environmental Protection, 2024)

Water-soluble biodegradable polyesters with pH and ionic responsivity - Xiao Li; Wei-Zhen Zheng; Peng-Yuan Xu; Ze-Yang Zhang; Ping-Li Wang; Bo Lu; Dan Huang; Zhi-Chao Zhen; Yang Zhao; Jun-Hui Ji; Ge-Xia Wang (Journal of Hazardous Materials, 2024)

Integrated biomarker-based ecological risks assessment of tadpole responses to tris(2-chloroethyl) phosphate, tris(1-chloro-2-propyl) phosphate, and their combined environmental exposure - Wen-Qi Xie; Zi-Ying Wang; Yi-Ge Xie; Jia-Jun Hao; Xin-Dan Cao; Zi-Yong Xiang; Lu-Ping Lou; Guo-Hua Ding (Environmental Pollution, 2024)

Smart contact Lenses: From rational design strategies to wearable health monitoring - Fei Han; Ping Ge; Fei Wang; Yanshen Yang; Shumeng Chen; Jing Kang; Yuan Ren; Hao Liu; Zhao Wei; Yuan He; Feng Xu (Chemical Engineering Journal, 2024)

Levels, sources, and health risk assessment of phthalate acid esters in indoor dust of various microenvironments in university - Jun Pan; Xin Li; Ping Ding; Haojie Luo; Sha Cai; Qing Ge; Liuyi Zhang; Guocheng Hu (Chemosphere, 2024)

Prevalence and molecular characteristics of intestinal pathogenic Escherichia coli isolated from diarrheal pigs in Southern China - Qian Li; Jing-Jing Dai; Shu-Yi Chen; Ruan-Yang Sun; Dong Wang; Shuan-Cheng Bai; Min-Ge Wang; Jian Sun; Xiao-Ping Liao; Ya-Hong Liu; Liang-Xing Fang (Veterinary Microbiology, 2024)

Beta-blocker drives the conjugative transfer of multidrug resistance genes in pure and complex biological systems - Qian Wu; Ge-Ge Wu; Kai-Nan Pan; Xue-Ping Wang; Hong-Yan Li; Zhe Tian; Ren-Cun Jin; Nian-Si Fan (Journal of Hazardous Materials, 2024)

Influence of community complexity and regulation by two-component system on community stability in aerobic composting in the presence of penicillin residues - Yuhao Guo; Ziliang Yin; Jie Kang; Xiujun Tu; Guoxu Ao; Jingping Ge; Wenxiang Ping (Journal of Cleaner Production, 2024)

Cactus-inspired moisture harvesting for sustainable and efficient high salinity desalination - Can Ge; Xianzhang Wu; Jiugang Li; Keshuai Liu; Duo Xu; Chong Gao; Yingcun Liu; Ping Sun; Ze Chen; Jian Fang (Desalination, 2024)

Mining for QTL controlling maize low-phosphorus response genes combined with deep resequencing of RIL parental genomes and in silico GWAS analysis - Bowen Luo; Peng Ma; Chong Zhang; Xiao Zhang; Jing Li; Junchi Ma; Zheng Han; Shuhao Zhang; Ting Yu; Guidi Zhang; Hongkai Zhang; Haiying Zhang; et al. (Theoretical and Applied Genetics, 2024)

Cyanidin prevents cardiomyocyte apoptosis in mice after myocardial infarction - Deng Gang; Ouyang Qing; Yongzheng Yang; Muqaddas Masood; Yu-Hong Wang; Jiang Linhui; Su Haotao; Ge Li; Chi Liu; Moussa Ide Nasser; Ping Zhu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Timing and Kinematics of late Cenozoic Strike-slip Faults in the Western Tibetan Plateau: New Constraints from Provenance Analysis and Detrital Thermochronology - Xiaochun Wei; Hanlin Chen; Rong Yang; Ping Wang; Shanying Li; Xuhua Shi; Jin Ge (Tectonophysics, 2024)

An engineered DNA aptamer-based PROTAC for precise therapy of p53-R175H hotspot mutant-driven cancer - Lingping Kong; Fanlu Meng; Ping Zhou; Ruixin Ge; Xiaoshan Geng; Zhihao Yang; Guo Li; Linlin Zhang; Jing Wang; Jinfeng Ma; Cheng Dong; Jun Zhou; et al. (Science Bulletin, 2024)

Anti-inflammatory discovery of sesquiterpenoids and a jasmonic acid derivative from Artemisia stolonifera - Ting Wu; Wen-Jing Wang; Zhou-Yuan Li; Yi-Tian Liu; Tian-Ping Yu; Shuang-Ge Li; Hong-Zhi Du; Chun Gui; Da-Hui Liu; Xiao-Long Yang (Phytochemistry, 2024)

How extreme hydrological events correspond to climate extremes in the context of global warming: A case study in the Luanhe River Basin of North China - Ge Gao; Jianzhu Li; Ping Feng; Jia Liu; Yicheng Wang (International Journal of Climatology, 2024)
The consensus on climate warming is well‐established, and extreme values inherently encapsulate more information than averages. Against the backdrop of frequent extreme climate events, studying extreme values holds profound significance. This study aims to reveal the characteristics of extreme climate events and their role in triggering extreme hydrological events in the typical North China basin, that is, the Luanhe River Basin. Trends of 25 extreme climate indices during 1960–2018 are analysed using the Sen's slope and MK significance test to study the changing characteristics of extreme climate. Characteristics of extreme flood and dry events are examined, encompassing trend analyses at different time scales (seasonal, interannual, decadal) and concentration analysis. Finally, and most significantly, correlation analysis is conducted on extreme climate indices and features of extreme hydrological events, followed by principal component analysis of extreme climate indices, to precisely quantify the impact of extreme climate on the occurrence of extreme hydrological events. The results indicate a warming trend in extreme temperature indices, with a more significant rise in minimum temperatures compared to maximum temperatures. There is a significant decrease in precipitation, but precipitation at higher magnitudes is less affected by the overall reduction in total precipitation. Extreme dry events have markedly increased, particularly concentrated in winter with delayed occurrences, primarily induced by extreme temperature events, that is, warming effects. Conversely, extreme flood events have significantly decreased, mainly concentrated in summer and early autumn, predominantly caused by extreme precipitation and extreme high‐temperature events. The climate and hydrological conditions in the study area have become more extreme and complex. Severe river droughts may occur more frequently in winter, while extreme flooding may happen in summer. Therefore, it is necessary to pay more attention to these developments.

High efficiency triethylamine gas sensor based on SmVO4 nano octahedron granules - Cheng Yu Xu; Shu Yi Ma; Tian Yuan Dong; Ji Ming Liu; Jin Sha Wei; Hong Tao Jiang; Ping Ni; Ge Ge Fan; Jia Yun Guo (Journal of Environmental Chemical Engineering, 2024)

Metagenomic profiles of the antimicrobial resistance in traditional Chinese fermented meat products: Core resistome and co-occurrence patterns - Tianming Qu; Ping Wang; Xiaomei Zhao; Lijiao Liang; Qinglong Ji; Yiqiang Ge; Ying Chen (International Journal of Food Microbiology, 2024)

Highly efficient non-doped organic light emitting diodes based on phenanthreneimidazole derivatives with hot exciton mechanism - Shuyuan Ge; Chunya Du; Zhuang Cheng; Yaxue Wang; Zijun Feng; Zhenyu Yan; Yin Hu; Ping Lu (Chemical Engineering Journal, 2024)

Genetic differences among populations of Gynura procumbens (Lour.) Merr - Jiangfan Yu; Xinjian Tan; Dunyuan Huang; Qiuping Zhong; Ping Gu; Youcheng Zhou; Linqing Cao; Liyun Wang; Xirui Wan; Chuansong Chen; Yaqi Yuan; Hongyan Guo; et al. (Genetic Resources and Crop Evolution, 2024)

Enhanced lipid productivity of Monoraphidium strains in co-cultures and their potential for biodiesel production - Yimeng Lin; Jing Xu; Jixin Liu; Han Wang; Jingping Ge; Wenxiang Ping (Algal Research, 2024)

The First Genome-Wide Survey of Shortbelly Eel (Dysomma anguillare Barnard, 1923) to Provide Genomic Characteristics, Microsatellite Markers and Complete Mitogenome Information - Tian-yan Yang; Zi-yan Zhu; Yu-ping Liu; Si-ge Wang (Biochemical Genetics, 2024)

Research progress on improving the freeze-drying resistance of probiotics: A review - Sitong Ge; Jiarun Han; Qiaoyu Sun; Qingqing Zhou; Zhongdu Ye; Ping Li; Qing Gu (Trends in Food Science & Technology, 2024)

Structure-activity relationship and mechanistic study of organotins as inhibitors of human, pig, and rat gonadal 3β-hydroxysteroid dehydrogenases - Peiyu Wang; Zhongyao Ji; Huiqian Chen; Sailing Chen; Chengshuang Pan; Qianjin Fei; Ren-shan Ge; Ping Duan; Linxi Li (Toxicology and Applied Pharmacology, 2024)

Glacier dam evolution and knickpoint migration in the Yarlung Tsangpo Gorge, eastern Himalayas, since the last glacial period - Ping Wang; Huiying Wang; Gang Hu; Tao Liu; Cuiping Li; Jintang Qin; Yukui Ge (Quaternary Science Reviews, 2024)

Highly modified cephalotane-type diterpenoids from Cephalotaxus fortunei var. alpina and C. sinensis - Zhan-Peng Ge; Jin-Biao Xu; Peng Zhao; Mai Xiang; Yu Zhou; Ze-Min Lin; Jian-Ping Zuo; Jin-Xin Zhao; Jian-Min Yue (Phytochemistry, 2024)

Three-dimensional multi-channel structure NiCo alloy used for boosting efficient overall water splitting - Fan Yang; Zelin Li; Fei Zhu; Xiaolong Chen; Songwei Ge; Fei Yin; Fairy Fan Yang; Rui Yang; Yanjing Liu; Lili Gao; Qiang Wang; Rui Feng; et al. (Fuel, 2024)

Combined neurotoxicity of aged microplastics and thiamethoxam in the early developmental stages of zebrafish (Danio rerio) - Yanan Sun; Ping Ding; Jiayi Zhang; Kexin Sun; Xintong Li; Qing Ge; Yao Dang; Yunjiang Yu; Guocheng Hu (Environmental Pollution, 2024)

Electrocatalytic reduction of simulated industrial CO2 and CO mixtures: Revising chronoamperometry to enable selective gas mixture reduction via cyclic voltammetry - Wen Qian Chen; Jit Loong Cyrus Foo; Li Ya Ge; Andrei Veksha; Wei-Ping Chan; Yafei Shen; Grzegorz Lisak (Chemical Engineering Journal, 2024)

Visually evaluating drug efficacy in living cells using COF-based fluorescent nanoprobe via CHA amplified detection of miRNA and simultaneous apoptosis imaging - Chuandong Ge; Zhe Chen; Heming Sun; Ping Sun; Jiayin Zhao; Yanjuan Wu; Jing Xu; Mingyang Zhou; Mingming Luan (Analytica Chimica Acta, 2024)

Exploring the release mechanism of micro/nanoplastics from different layers of masks in water: towards reduction of plastic contamination in masks - Wei Ge; Hao Liang; Ping Gao; Yan Li; Ningning Song; Juan Wu; Chao Chai (Environmental Science and Pollution Research, 2024)

Visualized Enzyme-Activated Fluorescence Probe for Accurately Detecting β-Gal in Living Cells and BALB/c Nude Mice - Xiaoli Huang; Le Chang; Jianxin Ge; Ping Wang; Rui Yin; Guanqi Liu; Guopin Wang (Journal of Fluorescence, 2024)

Methyl jasmonate promotes suberin biosynthesis by stimulating transcriptional activation of AchMYC2 on AchFHT in wound healing of kiwifruit - Xiaopeng Wei; Linyao Liu; Guo Liu; Ping Geng; Xiaobo Wei; Xing Yao; Jiaying Chen; Wenjie Gong; Zhenzhen Ge; Mengpei Liu; Linchun Mao (Postharvest Biology and Technology, 2024)

Synthesis and antifungal activity of 2,4-diacetylphloroglucinol analogues - Xi-Long Guo; Chun-Yan Zhao; Cui-Ping Zhang; Yi Zhu; Qing-Rong Wu; Yuan-Qing Zhou; Ya-Hong Fei; Fang Ge; Wei Shi (Phytochemistry Letters, 2024)

Host-guest synergistic hydrogen bond triggered signal amplification for visualizing the plant hormone salicylic acid - A-Ling Tang; Li-Long Zhang; Shuai Tan; Ping Yang; Wei Niu; Mei-Hong Ge; Lin-Lin Yang; Pei-Yi Wang; Li-Wei Liu; Xiang Zhou; Song Yang (Chemical Engineering Journal, 2024)

Ecological succession of abundant and rare subcommunities during aerobic composting in the presence of residual amoxicillin - Liangyang Mao; Jie Kang; Rui Sun; Jiaxin Liu; Jingping Ge; Wenxiang Ping (Journal of Hazardous Materials, 2024)

Reversible manipulation of liquid-liquid phase separation using a chemical-based chemiDroplet - Chao Tian; Shengpeng Wan; Yi Lu; Ping Wang; Xin Ge; Lan Fang (Science Bulletin, 2024)

Research and development of vortex suction dedusting device based on multi-factor horizontal response surface method - Shuaishuai Ren; Deji Jing; Shaocheng Ge; Mingxing Ma; Mohammad Waqar Ali Asad; Ping Chang (Journal of Cleaner Production, 2024)

Comparison of dye-based and probe-based RT-LAMP in detection of canine astrovirus - Haixiao Shen; Dequan Yang; Xin Li; Houbin Ju; Feifei Ge; Xianchao Yang; Jian Wang; Luming Xia; Hongjin Zhao; Ping Jiang (Archives of Virology, 2024)

Morphological and phylogenetic analyses reveal a new species of Anthracophyllum (Omphalotaceae, Agaricales) in Zhejiang Province, China - Wen-Juan Yang; Miao Xu; Jing Zhang; Fan Zhou; Zhi-Fang Le; Wen-Jun Tong; Hai-Yan Song; Zhuo-Han Jin; Qiu-Ge Cheng; Jian-Ping Zhou; Yang Gao; Zhi-Jun Zhai; et al. (Archives of Microbiology, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Exploring digital finance, financial regulations and carbon emission nexus: New insight from resources efficiency, industrial structure and green innovation in China - Siyuan Xuan; Wenfeng Ge; Ping Yang; Yunfeng Zhang (Resources Policy, 2024)

Isolation and identification of Chlorella sorokiniana HDMA-16 and its cultivation potential in flax retting wastewater - Meiqi Wang; Jing Xu; Jialin Zou; Hongzhi Ling; Jingping Ge; Yimeng Lin; Wenxiang Ping (Algal Research, 2024)

Synergistic benefits of Funneliformis mosseae and Bacillus paramycoides: Enhancing soil health and soybean tolerance to root rot disease - Zhichao Yang; Jie Kang; Zeming Ye; Wei Qiu; Jiaxin Liu; Xinbo Cao; Jingping Ge; Wenxiang Ping (Environmental Research, 2023)

Projecting spatiotemporal dynamics of severe fever with thrombocytopenia syndrome in the mainland of China - Fang‐Yu Ding; Hong‐Han Ge; Tian Ma; Qian Wang; Meng‐Meng Hao; Hao Li; Xiao‐Ai Zhang; Richard James Maude; Li‐Ping Wang; Dong Jiang; Li‐Qun Fang; Wei Liu (Global Change Biology, 2023)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease with increasing incidence and geographic extent. The extent to which global climate change affects the incidence of SFTS disease remains obscure. We use an integrated multi‐model, multi‐scenario framework to assess the impact of global climate change on SFTS disease in China. The spatial distribution of habitat suitability for the tick Haemaphysalis longicornis was predicted by applying a boosted regression tree model under four alternative climate change scenarios (RCP2.6, RCP4.5, RCP6.0, and RCP8.5) for the periods 2030–2039, 2050–2059, and 2080–2089. We incorporate the SFTS cases in the mainland of China from 2010 to 2019 with environmental variables and the projected distribution of H. longicornis into a generalized additive model to explore the current and future spatiotemporal dynamics of SFTS. Our results demonstrate an expanded geographic distribution of H. longicornis toward Northern and Northwestern China, showing a more pronounced change under the RCP8.5 scenario. In contrast, the environmental suitability of H. longicornis is predicted to be reduced in Central and Eastern China. The SFTS incidence in three time periods (2030–2039, 2050–2059, and 2080–2089) is predicted to be increased as compared to the 2010s in the context of various RCPs. A heterogeneous trend across provinces, however, was observed, when an increased incidence in Liaoning and Shandong provinces, while decreased incidence in Henan province is predicted. Notably, we predict possible outbreaks in Xinjiang and Yunnan in the future, where only sporadic cases have been reported previously. These findings highlight the need for tick control and population awareness of SFTS in endemic regions, and enhanced monitoring in potential risk areas.

Determination of niclosamide and its two metabolites in fish by molecularly imprinted microsphere-based pseudo-ELISA - Hao Zhe Hou; Yan Su; Ge Lin Liu; Yao Jia Peng; Jian Ping Wang (Food Additives & Contaminants: Part A, 2023)

All-natural environmentally degradable poly (butylene terephthalate-co-caprolactone): A theoretical and experimental study of its degradation properties and mechanisms - Peng-Yuan Xu; Ping-Li Wang; Tian-Yuan Liu; Zhi-Chao Zhen; Bo Lu; Dan Huang; Ge-Xia Wang; Jun-Hui Ji (Science of The Total Environment, 2023)

Bisphenol analogues inhibit human and rat 17β-hydroxysteroid dehydrogenase 1: 3D-quantitative structure-activity relationship (3D-QSAR) and in silico docking analysis - Sailing Chen; Shaowei Wang; Jingyi Zheng; Han Lu; Huiqian Chen; Yunbing Tang; Nan Wang; Yang Zhu; Yiyan Wang; Ping Duan; Ren-shan Ge (Food and Chemical Toxicology, 2023)

Whole-Genome Sequence and Pathogenicity Analysis of Providencia Heimbachae Causing Diarrhea in Weaned Piglets - Kongrui Xiang; Zhuo Zhang; Nuowa Li; Ping Zhang; Feng Liu; Hai Li; Haoyuan Duan; Chuankun Zhang; Junwei Ge (Current Microbiology, 2023)

Temporal-spatial Generation of Astrocytes in the Developing Diencephalon - Wentong Hong; Pifang Gong; Xinjie Pan; Zhonggan Ren; Yitong Liu; Guibo Qi; Jun-Liszt Li; Wenzhi Sun; Woo-Ping Ge; Chun-Li Zhang; Shumin Duan; Song Qin (Neuroscience Bulletin, 2023)
Astrocytes are the largest glial population in the mammalian brain. However, we have a minimal understanding of astrocyte development, especially fate specification in different regions of the brain. Through lineage tracing of the progenitors of the third ventricle (3V) wall via in-utero electroporation in the embryonic mouse brain, we show the fate specification and migration pattern of astrocytes derived from radial glia along the 3V wall. Unexpectedly, radial glia located in different regions along the 3V wall of the diencephalon produce distinct cell types: radial glia in the upper region produce astrocytes and those in the lower region produce neurons in the diencephalon. With genetic fate mapping analysis, we reveal that the first population of astrocytes appears along the zona incerta in the diencephalon. Astrogenesis occurs at an early time point in the dorsal region relative to that in the ventral region of the developing diencephalon. With transcriptomic analysis of the region-specific 3V wall and lateral ventricle (LV) wall, we identified cohorts of differentially-expressed genes in the dorsal 3V wall compared to the ventral 3V wall and LV wall that may regulate astrogenesis in the dorsal diencephalon. Together, these results demonstrate that the generation of astrocytes shows a spatiotemporal pattern in the developing mouse diencephalon.

Genomic characterization and phylogenetic analysis of Aleutian mink disease virus identified in a sudden death mink case - Xingyang Cui; Yan Yang; Fang Wang; Jilong Luo; Ping Zhang; Hongyan Chen; Lili Zhao; Junwei Ge (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Highly efficient non-doped deep-blue organic light-emitting diodes based on pyreneimidazole derivative with external quantum efficiency > 11% and negligible efficiency roll-off - Zhuang Cheng; Chunya Du; Shuyuan Ge; Yaxue Wang; Futong Liu; Yulei Chang; Ying Lv; Ping Lu (Chemical Engineering Journal, 2023)

Divergent accumulation of microbial and plant necromass along paddy soil development in a millennium scale - Yalong Liu; Ping Wang; Guan Cai; Tida Ge; Jingkuan Wang; Georg Guggenberger (Soil and Tillage Research, 2023)

Reconstructing post-mid Pleistocene glacial-dammed paleolakes in the Tsangpo Gorge, southeastern Tibetan Plateau - Ping Wang; Huiying Wang; Gang Hu; Yukui Ge; Tao Liu; Bo Xu (Quaternary Science Reviews, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Benfotiamine attenuates the high-carbohydrate diet-induced mitochondrial redox imbalance in fish Megalobrama amblycephala by activating SIRT3 - Ling Zhang; Ya-Ping Ge; Yang-Yang Huang; Wei-Liang Chen; Wen-Bin Liu; Ding-Dong Zhang; Xiang-Fei Li (Aquaculture, 2023)

Fluorescence tracing the degradation process of biodegradable PBAT: Visualization and high sensitivity - Tian-Yuan Liu; Zhi-Chao Zhen; Xiao-Ling Zang; Peng-Yuan Xu; Ge-Xia Wang; Bo Lu; Fei Li; Ping-Li Wang; Dan Huang; Jun-Hui Ji (Journal of Hazardous Materials, 2023)

Evaluation on the rejuvenation and diffusion characteristics of waste cooking oil on aged SBS asphalt based on molecular dynamics method - Huanan Yu; Jinguo Ge; Guoping Qian; Chao Zhang; Wan Dai; Ping Li (Journal of Cleaner Production, 2023)

In situ assembly of graphitic carbon nitride/polypyrrole in a thin-film nanocomposite membrane with highly enhanced permeability and durability - Mengni Ge; Zhuohui Jia; Yan Yang; Ping Dong; Chao Peng; Xi Zhang; Raf Dewil; Yan Zhao; Bart Van der Bruggen; Jianfeng Zhang (Desalination, 2023)

Decadal difference in influential factors for interannual variations of winter Tibetan Plateau snow - Changyan Zhou; Ping Zhao; Ge Liu; An Xiao; Haohui Yu (Atmospheric Research, 2023)

How to drive strategic green innovation behavior? A qualitative comparative analysis (QCA) based on Chinese manufacturing enterprises - Jing Xiao; Ping Zeng; Ge Ren; Leimin Zhang (Environmental Science and Pollution Research, 2023)

Residence time of carbon in paddy soils - Yalong Liu; Tida Ge; Ping Wang; Kees Jan van Groenigen; Xuebin Xu; Kun Cheng; Zhenke Zhu; Jingkuan Wang; Georg Guggenberger; Ji Chen; Yiqi Luo; Yakov Kuzyakov (Journal of Cleaner Production, 2023)

NH3 and N2O emission durability of the heavy-duty diesel engine with DOC, DPF, SCR, and ASC through the accelerated aging method - Liqun Lyu; Wenqiang Sun; Ping Feng; Huaiyu Wang; Lijun Hao; Jianwei Tan; Xin Wang; Chao Song; Haixia Li; Zhao Li; Jiaxing Wang; Yunshan Ge (Fuel, 2023)

Rotational performance of semi-rigid plate-type joints for reticulated shell structures composed of plate members - Hui-Bin Ge; Hua-Ping Wan; Yanbin Shen; Chao Yang; Yaozhi Luo (Engineering Structures, 2023)

Aerobic composting with sauerkraut fermentation waste water: Increasing the stability and complexity of bacterial community and changing bacterial community assembly processes - Jie Kang; Gang Song; Xu Wang; Wei Qiu; Fangyi Pei; Hongzhi Ling; Wenxiang Ping; Jingping Ge (Bioresource Technology, 2023)

Synthesis and biological evaluation of esculetin derivatives as potential anti-HBV agents - Zhen Ye; Tong-Shi-Yao Zhao; Shan-Bin Li; Xian-Li Zhou; Qin Luo; Jiang-Ke Qin; Cheng-Qin Liang; Ping Wang; Guang-Bo Ge (Medicinal Chemistry Research, 2023)

OsCYBDOMG1, a cytochrome b561 domain-containing protein, regulates salt tolerance and grain yield in rice - Ping Deng; Chengjuan Cao; Xingyu Shi; Qun Jiang; Jinjin Ge; Like Shen; Chunxia Guo; Ling Jiang; Wen Jing; Wenhua Zhang (Theoretical and Applied Genetics, 2023)

Isothermal exponential amplification reactions triggered by circular templates (cEXPAR) targeting miRNA - Xue-mei Qu; Xiao-dong Ren; Ning Su; Xian-ge Sun; Shao-li Deng; Wei-ping Lu; Qing Huang (Molecular Biology Reports, 2023)

Applications of bioremediation and phytoremediation in contaminated soils and waters: CREST publications during 2018–2022 - Chen-Jing Liu; Song-Ge Deng; Chun-Yan Hu; Peng Gao; Eakalak Khan; Chang-Ping Yu; Lena Q. Ma (Critical Reviews in Environmental Science and Technology, 2023)

The essentiality of dietary myo-inositol to oriental river prawn (Macrobrachium nipponense): Evidence in growth performance, lipid metabolism and mitochondrial function - Ming-Yang Liu; Miao Sun; Ling Zhang; Ya-Ping Ge; Bo Liu; Xiang-Fei Li (Aquaculture, 2023)

Transition of source/sink processes and fate of ammonium in groundwater along with redox gradients - Li-Li Han; Helin Wang; Lianghao Ge; Min Nina Xu; Jin-Ming Tang; Li Luo; Ping Li; Shuh-Ji Kao (Water Research, 2023)

Influence mechanism of ammonia mixing on NO formation characteristics of pulverized coal combustion and N oxidation in ammonia-N/coal-N - Ping Chen; Changhao Hua; Boyu Jiang; Mingyan Gu; Zhenling Ge; Meng Zhang; Kun Luo; Jianren Fan; Yi Wang (Fuel, 2023)

24-Epibrassinolide Enhances Resistance Against Colletotrichum fructicola by Promoting Lignin Biosynthesis in Camellia sinensis L. - Lan Zhang; Zheng Zhang; Golam Jalal Ahammed; Xiaorong Wang; Huihan Fang; Peng Yan; Li-Ping Zhang; Shibei Ge; Jianyu Fu; Wen-Yan Han; Xin Li (Journal of Plant Growth Regulation, 2023)

Enhanced Lipid Productivity in Low-Starch Mutant of Monoraphidium sp. for Biodiesel Production - Yimeng Lin; Yunye Zhang; Yang Fan; Chang Li; Hongzhi Ling; Wenxiang Ping; Jingping Ge (BioEnergy Research, 2023)

Dopaminergic Dysfunction and Glucose Metabolism Characteristics in Parkin-Induced Early-Onset Parkinson’s Disease Compared to Genetically Undetermined Early-Onset Parkinson’s Disease - Feng-Tao Liu; Jia-Ying Lu; Yi-Min Sun; Ling Li; Yu-Jie Yang; Jue Zhao; Jing-Jie Ge; Ping Wu; Jie-Hui Jiang; Jian-Jun Wu; Chuan-Tao Zuo; Jian Wang (Phenomics, 2023)

Bi/Te control on gold mineralizing processes in the North China Craton: Insights from the Wulong gold deposit - Haoxuan Feng; Ping Shen; Rixiang Zhu; Andrew G. Tomkins; Joël Brugger; Ge Ma; Changhao Li; Yang Wu (Mineralium Deposita, 2023)

The combined effect of deoxynivalenol and Fumonisin B1 on small intestinal inflammation mediated by pyroptosis in vivo and in vitro - Xinru Mao; Ping Zhang; Heng Du; Lei Ge; Shuiping Liu; Kehe Huang; Xingxiang Chen (Toxicology Letters, 2023)

Valence engineering at the interface of MoS2/Mo2C heterostructure for bionic nitrogen reduction - Tong Ye; Kun Ba; Xiaoyong Yang; Taishi Xiao; Yangye Sun; Hanqi Liu; Can Tang; Binghui Ge; Ping Zhang; Tao Duan; Zhengzong Sun (Chemical Engineering Journal, 2023)

Inhibition of Spinal 5-HT3 Receptor and Spinal Dorsal Horn Neuronal Excitability Alleviates Hyperalgesia in a Rat Model of Parkinson’s Disease - Cheng-Jie Li; Li-Ge Zhang; Lu-Bing Liu; Meng-Qi An; Li-guo Dong; Han-Ying Gu; Yong-Ping Dai; Fen Wang; Cheng-Jie Mao; Chun-Feng Liu (Molecular Neurobiology, 2022)

Precise ages of gold mineralization and pre-gold hydrothermal activity in the Baiyun gold deposit, northeastern China: in situ U–Pb dating of hydrothermal xenotime and rutile - Haoxuan Feng; Ping Shen; Rixiang Zhu; Jian-Wei Zi; David I. Groves; Changhao Li; Yang Wu; Ge Ma; Taiyang Li (Mineralium Deposita, 2022)

Feed types affect the growth, nutrient utilization, digestive capabilities, and endocrine functions of Megalobrama amblycephala: a comparative study between pelleted and extruded feed - Chao-Fan He; Xiang-Fei Li; Guang-Zhen Jiang; Ling Zhang; Miao Sun; Ya-Ping Ge; Wei-Liang Chen; Wen-Bin Liu (Fish Physiology and Biochemistry, 2022)

Testing environmental Kuznets curve hypothesis: considering the impact of Sino-US trade on three main industries in China - Long-kang Wu; Tian-tian Feng; Hui Luo; Xiao-lei Gong; Jian-ping Ge (Environmental Science and Pollution Research, 2022)

Male Predisposition in Cerebellar Mutism Syndrome: a Cohort Study - Wei Yang; Ming Ge; Kaiyi Zhu; Jiashu Chen; Ping Yang; Yingjie Cai; XiaoJiao Peng; Jia Wang; Hailang Sun; Yuanqi Ji; Fengmao Zhao; Hong Zhang (The Cerebellum, 2022)

Ultrasound-induced biophysical effects in controlled drug delivery - Lulu Zhang; Zhuohua Lin; Lan Zeng; Fan Zhang; Lihong Sun; Suhui Sun; Ping Wang; Menghong Xu; Jinxia Zhang; Xiaolong Liang; Huiyu Ge (Science China Life Sciences, 2022)

Screening of Biological Target Molecules Related to Glucocorticoid-Induced Cataract (GIC) on the Basis of Constructing ceRNA Network - Zhan Shi; Xiumei Zhao; Ying Su; Chao Wang; Ping Liu; Hongyan Ge (Biochemical Genetics, 2022)

Comparative Transcriptomic and Proteomic Analysis of Exopalaemon carinicauda in Response to Alkalinity Stress - Zhen Qin; Qianqian Ge; Jiajia Wang; Mingdong Li; Ping Liu; Jian Li; Jitao Li (Frontiers in Marine Science, 2021)
Saline-alkaline waters are stressful environments where most aquatic animals can’t survive normally, and alkalinity is one of the key limited environmental factors. Due to strong adaptability to environment, the ridgetail white prawn Exopalaemon carinicauda is a potential good species suitable for large-scale culture in saline-alkaline waters. Exploring its alkaline adaptability mechanism will help to guide more marine crustaceans to saline-alkaline culture. In this study, an integrative analysis of the gill-specific transcriptome and proteome at 0, 12, and 36 h after alkalinity stress was performed to identify important regulators and pathways involved in alkalinity adaption of E. carinicauda . A total of 3,157 differentially expressed genes (DEGs) and 443 differentially expressed proteins (DEPs) were identified at 12 and 36 h compared with 0 h. Base on the transcriptome analysis, the Gene Ontology (GO) enriched terms were mainly related to ion transport, including “calcium-transporting ATPase activity,” “ATPase coupled ion transmembrane transporter activity,” “divalent inorganic cation transmembrane transporter activity,” etc., and the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways mainly refer to the processes of endocrine system at both 12, and 36 h. Based on the proteomic analysis, KEGG pathways related to lipolysis and amino acids metabolism were significantly enriched at 12 h, and carbohydrate metabolism and immune response were significantly enriched at 36 h. There were significantly up-regulated expressions of ion transport related genes including aquaporin, carbonic anhydrase, ammonium transporter Rh type A-like, Na + /H + -exchanger, etc., as well as ion transport proteins including V-type proton ATPase 116 kDa subunit a-like isoform X1, sodium-potassium ATPase beta, vesicle associated membrane protein, etc. after alkalinity exposure, which indicating their important roles in response to alkalinity stress. The results of integrated analysis between proteome and transcriptome showed that up-regulated DEG/DEP (aldehyde dehydrogenase) was significantly enriched at 12 h and the up-regulated DEG/DEP (peptidylglycine alpha) was significantly enriched at 36 h, suggesting the two molecules may be critical in response to alkalinity change. This study reveals the first time-course, gill-specific, combined transcriptomic and proteomic profiling associated with alkalinity adaption of E. carinicauda and provides new insights into the mechanisms underlying the molecular response to alkalinity stress in shrimp.

Characterization of a novel shrimp pathogen, Vibrio brasiliensis , isolated from Pacific white shrimp, Penaeus vannamei - Ge Li; Guosi Xie; Hailiang Wang; Xiaoyuan Wan; Xinshu Li; Chengyin Shi; Ziyan Wang; Miao Gong; Ting Li; Ping Wang; Qingli Zhang; Jie Huang (Journal of Fish Diseases, 2021)
A novel pathogenic strain Vibrio 20190611023 was isolated from the hepatopancreas of moribund cultured Penaeus vannamei suffering from black gill disease. This strain was identified as V . brasiliensis based on the phylogenetic analyses of 16S rDNA gene and five other housekeeping genes (i.e., gapA , ftsZ , mreB , topA and gyrB ). Some biochemical features of this strain were determined with an API 20NE system, and its haemolytic activity was determined using a sheep blood agar plate. The pathogenicity of this isolate 20190611023 was confirmed by the experimental challenge tests and histopathological examinations. P. vannamei were challenged via reverse gavage with different doses of bacterial suspensions. The calculated median lethal dose (LD 50 ) was (3.16 ± 1.78) × 10 5 CFU/g (body weight). Moreover, antibiotic susceptibility tests were performed, the results of which showed that the strain 20190611023 was sensitive to chloramphenicol, compound sulphamethoxazole, ciprofloxacin, doxycycline and oxacillin, but resistant to erythromycin, kanamycin, gentamicin, cefoperazone, ceftriaxone, cefamezin and piperacillin. To our knowledge, this is the first report for demonstrating V . brasiliensis as a shrimp pathogen, which expands the host range of V . brasiliensis infection. The present study highlights that more attention should be paid to this novel pathogen in intensive shrimp aquaculture.

3D DEM analysis on tractive trafficability of a lunar rover wheel with bionic wheel lugs - Hao Pang; Rui Zhang; Ping Ge; Fang Liu; Chengjin Wang; Wenchao Dong; Tao Li; Jianqiao Li (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)

Molecular cloning and functional characterization of the hypoxia-inducible factor-1α in bighead carp (Aristichthys nobilis) - Yan Lin; Ling-Hong Miao; Bo Liu; Bing-Wen Xi; Liang-Kun Pan; Xian-Ping Ge (Fish Physiology and Biochemistry, 2021)

Pregabalin-associated stuttering and frequent blepharospasm: case report and review. - Lingzhi Ge; Ang Li; Ni Wang; Ping Li; Hongyan Xin; Wenfei Li (DARU Journal of Pharmaceutical Sciences, 2020)
Herpes zoster is an acute, painful, herpes skin disease caused by varicella-zoster virus, which may cause viral meningitis. Pregabalin has been shown to be efficacious in the treatment of pain in patients with herpes zoster. However, it has the side effects of neurotoxicity. We describe a 68-year-old female patient with herpes zoster, and she was treated with pregabalin. The patient presented with stuttering and frequent blepharospasm after 3 days of pregabalin treatment. Pregabalin was discontinued, the symptoms of stuttering and frequent blepharospasm completely resolved without any special treatment after one week. In this case, the etiology of stuttering and frequent blepharospasm may be related to pregabalin. Clinicians should be alert to the rare symptoms associated with the use of pregabalin.

What factors determine the mass elevation effect of the Tibetan Plateau? - Fang Han; Li Wan; Hong-zhi Wu; Bai-ping Zhang; Lan Gao; Ge Song (Journal of Mountain Science, 2020)

Toxic effects of heavy metals on the freshwater benthic organisms in sediments and research on quality guidelines in Poyang Lake, China - Ping Zhang; Xuemei Pan; Qinyuan Wang; Gang Ge; Yun Huang (Journal of Soils and Sediments, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Disruption of the lactate dehydrogenase and acetate kinase genes in Klebsiella pneumoniae HD79 to enhance 2,3-butanediol production, and related transcriptomics analysis - Jingping Ge; Jiawang Wang; Guangbin Ye; Shanshan Sun; Rui Guo; Gang Song; Wenxiang Ping (Biotechnology Letters, 2020)

Impact of prolonged rice cultivation on coupling relationship among C, Fe, and Fe-reducing bacteria over a 1000-year paddy soil chronosequence - Yalong Liu; Yuqi Dong; Tida Ge; Qaiser Hussain; Ping Wang; Jingkuan Wang; Yong Li; Georg Guggenberger; Jinshui Wu (Biology and Fertility of Soils, 2019)

Synthesis and antitumor activity of cyclic octapeptide, samoamide A, and its derivatives - Fei Ge; Chi Zhang; Longbao Zhu; Wanzhen Li; Ping Song; Yugui Tao; Guocheng Du (Medicinal Chemistry Research, 2019)

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy - Zheng Zhang; Shi-min Jiang; Ye-ping Ma; Pei-lin Dai; Yi-ning Wang; Gu-ming Zou; Hong-mei Gao; Yue Yang; Wen-ge Li (Molecular and Cellular Biochemistry, 2019)

Improving remote sensing-based net primary production estimation in the grazed land with defoliation formulation model - Hui Ye; Xiao-tao Huang; Ge-ping Luo; Jun-bang Wang; Miao Zhang; Xin-xin Wang (Journal of Mountain Science, 2019)

Effect of nitrite exposure on oxygen-carrying capacity and gene expression of NF-κB/HIF-1α pathway in gill of bighead carp (Aristichthys nobilis) - Yan Lin; Ling-Hong Miao; Wu-Xiao Zhang; Wen-Jing Pan; Hua-Liang Liang; Xian-Ping Ge; Yan-Shun Xu; Bo Liu; Ming-Chun Ren; Qun-Lan Zhou; Si-Lei Xia (Aquaculture International, 2018)

Depth treatment of coal-chemical engineering wastewater by a cost-effective sequential heterogeneous Fenton and biodegradation process - Yili Fang; Weizhao Yin; Yanbin Jiang; Hengjun Ge; Ping Li; Jinhua Wu (Environmental Science and Pollution Research, 2018)

Recent advances in enhanced enzyme activity, thermostability and secretion by N-glycosylation regulation in yeast - Fei Ge; Longbao Zhu; Anna Aang; Ping Song; Wanzhen Li; Yugui Tao; Guocheng Du (Biotechnology Letters, 2018)

Two new species of Pustula (Albuginales, Oomycota) from Junggar Basin in China based on morphology and molecular data - Biao Xu; Young Joon Choi; Jia Ge Song; Shan He Zhang; Ping Gen Xi; Hyeon Dong Shin; Zi De Jiang (Mycological Progress, 2018)

Different behavioral, neural and neuropeptide responses of fathers to their own and to alien pups in mandarin voles - Wei Yuan; Xiang-Ping Yang; Peng Yu; Rui Jia; Fa-Dao Tai; Bin Wei; Xiao Liu; Lei-Ge Ma (Journal of Comparative Physiology A, 2018)

A Fluorescent Sensor of 3-Aminobenzeneboronic Acid Functionalized Hydrothermal Carbon Spheres for Facility Detection of L-tryptophan - Rui Zhang; Li-Xia Wang; Yun-Di Zhang; Chun-Hua Ge; Jia-Ping Wang; Ying Zhang; Xiang-Dong Zhang (Journal of Fluorescence, 2018)

ALDH2 genes are negatively correlated with natural deastringency in Chinese PCNA persimmon (Diospyros kaki Thunb.) - Jun-Chi Xu; Jin-Ge Ding; Jian-Ping Gan; Rong-Li Mo; Li-Qing Xu; Qing-Lin Zhang; Zheng-Rong Luo (Tree Genetics & Genomes, 2017)

Establishing a Forecast Mathematical Model of Sugarcane Yield and Brix Reduction Based on the Extent of Pokkah Boeng Disease - Ze-ping Wang; Lu Liu; Yu-chi Deng; Yi-jie Li; Ge-min Zhang; Shan-hai Lin; Tie-guang He (Sugar Tech, 2017)

Cross-neutralization of SARS coronavirus-specific antibodies against bat SARS-like coronaviruses - Lei-Ping Zeng; Xing-Yi Ge; Cheng Peng; Wanbo Tai; Shibo Jiang; Lanying Du; Zheng-Li Shi (Science China Life Sciences, 2017)

Monoclonal antibody-based serological assays for detection of Potato virus S in potato plants - Ge Song; Jia-yu Wu; Yan Xie; Yong Liu; Ya-juan Qian; Xue-ping Zhou; Jian-xiang Wu (Journal of Zhejiang University-SCIENCE B, 2017)

Bioinformatic prediction and analysis of glucolipid metabolic regulation by miR-34a in Megalobrama amblycephala - Ling-Hong Miao; Wen-Jing Pan; Yan Lin; Xian-Ping Ge; Bo Liu; Ming-Chun Ren; Qun-Lan Zhou (Genes & Genomics, 2017)

Artepillin C, is it a good marker for quality control of Brazilian green propolis? - Cui-ping Zhang; Xiao-ge Shen; Jia-wei Chen; Xia-sen Jiang; Kai Wang; Fu-liang Hu (Natural Product Research, 2017)

Aberrant Axonal Arborization of PDF Neurons Induced by Aβ42-Mediated JNK Activation Underlies Sleep Disturbance in an Alzheimer’s Model - Qian Song; Ge Feng; Zehua Huang; Xiaoman Chen; Zhaohuan Chen; Yong Ping (Molecular Neurobiology, 2017)

Sharp genetic discontinuity in the aridity‐sensitive Lindera obtusiloba (Lauraceae): solid evidence supporting the Tertiary floral subdivision in East Asia - Jun‐Wei Ye; Wei‐Ning Bai; Lei Bao; Tian‐Ming Wang; Hong‐Fang Wang; Jian‐Ping Ge (Journal of Biogeography, 2017)
Aim Investigating phytogeographical divides can help provide a better understanding of the evolution of floras. Tertiary relict floras in East Asia have been subdivided into a northern region ( NEA ) and a southern region ( SEA ), separated by an arid belt, although this division remains little‐studied since it was proposed in 2002. To test its validity, we investigated the evolutionary history of a Tertiary relict species, Lindera obtusiloba . Location East Asia. Methods Chloroplast DNA (cp DNA ) and nuclear microsatellites ( nSSR s) were genotyped in 34 populations. Regional genetic diversities were compared, and genetic differentiation was calculated between and within regions. Bayesian phylogenetics and Bayesian clustering were employed for phylogeographic reconstruction. The time to the most recent common ancestor ( TMRCA ) and divergence time between the two regions were estimated. Historical rates of gene flow were calculated using the maximum‐likelihood method. The potential habitat at present, during the Last Glacial Maximum ( LGM ) and during the Last Interglacial ( LIG ) were predicted by ecological niche modelling ( ENM ). Results Both markers revealed sharp genetic discontinuities and limited migration between regions. The TMRCA and population divergence can probably both be dated to the Pliocene. Clear genetic structure was found within each region. The genetic diversity of both markers and the age of chlorotypes decreased with increasing longitude within SEA . Japan harboured the highest genetic diversity within NEA , with abundant private and ancestral chlorotypes. NEA had greater genetic diversity than SEA in nSSR s, whereas the opposite was true for cp DNA . ENM in LGM and LIG may support long‐term isolation in multiple locations in both regions. Main conclusions Our study provides solid evidence for the proposed floral subdivision along the arid belt within East Asia. Populations in both regions remained stable over a long period and sustained multiple glacial refugia. Westernmost SEA and easternmost NEA sustained ancestral populations. Clear eastward expansion was detected within SEA .

Dispersal modality determines the relative partitioning of beta diversity in spider assemblages on subtropical land‐bridge islands - Lingbing Wu; Xingfeng Si; Raphael K. Didham; Dapeng Ge; Ping Ding (Journal of Biogeography, 2017)
Aim To identify geographical drivers determining the relative partitioning of species replacement and richness difference or nestedness‐resultant components of beta diversity in spider groups with differing dispersal modalities. Location Thousand Island Lake, China. Methods We sampled spider assemblages on 31 land‐bridge islands for two years. Each species was classified into a dispersal group based on ballooning propensity (frequent, occasional or non‐ballooners). Two frameworks were used to separate beta diversity (β cc or β jac ) of each group into either species replacement (β ‐3 ) and richness difference (β rich ) components, or turnover (β jtu ) and nestedness‐resultant (β jne ) components. Mantel and partial Mantel tests were performed to determine correlations between pairwise dissimilarities and difference in island area, difference in distance to mainland and inter‐island distance for each group. Results The multiple‐island dissimilarity of spiders was primarily driven by turnover. Beta diversity (β cc or β jac ) was positively associated with difference in island area in frequent ballooners, and negatively associated with difference in island area in occasional ballooners. Difference in island area had positive effects on β jne for all groups, but negative effects on β ‐3 and β jtu for occasional or non‐ballooners. β rich was positively associated with difference in island area in frequent and non‐ballooners. We did not find any significant isolation effects for these three measures of dissimilarity. Main conclusions The dominant process of extinction resulted in a high contribution of turnover to the multiple‐island dissimilarity of spiders. Specifically, frequent ballooners contributed less turnover to multiple‐island dissimilarity than occasional and non‐ballooners. The most likely explanation for this is that frequent ballooners were potentially able to colonize all islands, whereas occasional and non‐ballooners were constrained by water barriers and were unable to occupy most islands. Contrasting dissimilarities among dispersal groups of spiders demonstrates the importance of beta diversity partitioning, and the mechanistic insight gained on trait‐dependence in community assembly.

Fate of rice shoot and root residues, rhizodeposits, and microbial assimilated carbon in paddy soil - part 2: turnover and microbial utilization - Zhenke Zhu; Tida Ge; Yajun Hu; Ping Zhou; Tingting Wang; Olga Shibistova; Georg Guggenberger; Yirong Su; Jinshui Wu (Plant and Soil, 2017)

Corncob Mild Alkaline Pretreatment for High 2,3-Butanediol Production by Spent Liquor Recycle Process - HongZhi Ling; KeKe Cheng; JingPing Ge; WenXiang Ping (BioEnergy Research, 2017)

Cultivation of green algae Platymonas helgolandica in rearing water enhances the growth performance and resistance of Litopenaeus vannamei against Vibrio parahaemolyticus infection - Hongxing Ge; Jian Li; Ping Chen; Zhiqiang Chang; Mingming Shen; Fazhen Zhao (Aquaculture International, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

NF-κB is involved in the LPS-mediated proliferation and apoptosis of MAC-T epithelial cells as part of the subacute ruminal acidosis response in cows - Wen-Jie Fan; He-Ping Li; He-Shui Zhu; Shi-Ping Sui; Pei-Ge Chen; Yue Deng; Tong-Ming Sui; Yue-Ying Wang (Biotechnology Letters, 2016)

Chain elongation analog of resveratrol as potent cancer chemoprevention agent - Yan-Fei Kang; Hai-Xia Qiao; Long-Zuo Xin; Li-Ping Ge (Journal of Physiology and Biochemistry, 2016)

Illicit drugs and their metabolites in 36 rivers that drain into the Bohai Sea and north Yellow Sea, north China - De-Gao Wang; Qiu-Da Zheng; Xiao-Ping Wang; Juan Du; Chong-Guo Tian; Zhuang Wang; Lin-Ke Ge (Environmental Science and Pollution Research, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

Effects of fish meal replacement by soybean peptide on growth performance, digestive enzyme activities, and immune responses of yellow catfish Pelteobagrus fulvidraco - Zhen-xin Zhao; Chang-you Song; Jun Xie; Xian-ping Ge; Bo Liu; Si-lei Xia; Shun Yang; Qing Wang; Sai-hua Zhu (Fisheries Science, 2016)

The Oldest Cranium of Sinomastodon (Proboscidea, Gomphotheriidae), Discovered in the Uppermost Miocene of Southwestern China: Implications for the Origin and Migration of This Taxon - Shi-Qi Wang; Xue-Ping Ji; Nina G. Jablonski; Denise F. Su; Jun-Yi Ge; Chang-Fen Ding; Teng-Song Yu; Wen-Qi Li; Jaroon Duangkrayom (Journal of Mammalian Evolution, 2016)

Interaction of TIM4 and TIM3 induces T helper 1 cell apoptosis - Rong-Ti Ge; Lu Zeng; Li-Hua Mo; Ling-Zhi Xu; Huan-Ping Zhang; Hai-Qiong Yu; Min Zhang; Zhi-Gang Liu; Zhan-Ju Liu; Ping-Chang Yang (Immunologic Research, 2016)

Growth performance and immune responses of gibel carp, Carassius auratus gibelio, fed with graded level of rare earth-chitosan chelate - Qun-lan Zhou; Jun Xie; Xian-ping Ge; H. Michael Habte-Tsion; Bo Liu; Mingchun Ren (Aquaculture International, 2016)

Quasi-Saturated Zones Induced by Rainfall Infiltration - Sun Dong-mei; Zang Yong-ge; Feng Ping; Stephan Semprich (Transport in Porous Media, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

The complete mitochondrial genome of fall armyworm Spodoptera frugiperda (Lepidoptera:Noctuidae) - Qiu-Ning Liu; Xin-Yue Chai; Dan-Dan Bian; Bao-Ming Ge; Chun-Lin Zhou; Bo-Ping Tang (Genes & Genomics, 2016)

Anomalies of Northern Hemisphere ozone associated with a tropopause‐lower stratosphere teleconnection during summer - Yuanxiang Wang; Ping Zhao; Haiming Xu; Ge Liu (International Journal of Climatology, 2016)
Using the ozone data set from the satellite observations and the atmospheric reanalysis data sets during 1979–2005, we examine the variability of a tropopause‐lower stratosphere (TS) teleconnection a and its relationship with the ozone change over the Northern Hemisphere ( NH ) during summer. The TS teleconnection has an approximate opposite phase to that in the upper‐troposphere Asian‐Pacific Oscillation ( APO ), and the TS teleconnection index (the TS index) is also related well to the APO index. Corresponding to a higher TS index, the ozone generally decreases in the NH mid‐high latitudes (near 40°N and the Far East of Russia). This link between the TS teleconnection and the ozone is physically supported by the changes of the background atmospheric circulation. When the TS index is higher, the decrease of the ozone is closely associated with an increase of the local tropopause height. The upward and downward motion variations in the upper troposphere and the lower stratosphere in the east and west parts of the anomalous anticyclones associated with the TS index strengthen the exchanges of the ozone between the troposphere and the lower stratosphere, which may cause a decrease of the ozone. The horizontal advection of the ozone could also contribute to the ozone decreases over these regions.

Gomisin A is a Novel Isoform-Specific Probe for the Selective Sensing of Human Cytochrome P450 3A4 in Liver Microsomes and Living Cells - Jing-Jing Wu; Guang-Bo Ge; Yu-Qi He; Ping Wang; Zi-Ru Dai; Jing Ning; Liang-Hai Hu; Ling Yang (The AAPS Journal, 2016)

New norditerpenoid alkaloids from Aconitum vilmorinianum Komarov - Cui-Ling Chen; Wen-Hong Tan; Yan Wang; Zhi-Ge Xue; Chun-Ping Wan; Zhu-Ya Yang; Zhi-Hong Zhou; Xiao-Xia Ma (Journal of Natural Medicines, 2015)

Prestack forward modeling of tight reservoirs based on the Xu–White model - Chao Zhu; Qing-Xin Guo; Qing-Shun Gong; Zhan-Guo Liu; Sen-Ming Li; Ge-Ping Huang (Applied Geophysics, 2015)

Enhanced Phytoextraction of Heavy Metals from Contaminated Soil by Plant Co-cropping Associated with PGPR - Zhi-feng Liu; Hong-guang Ge; Chen Li; Zuo-ping Zhao; Feng-min Song; Shi-bin Hu (Water, Air, & Soil Pollution, 2015)

Paleoclimate modeling in China: A review - Dabang Jiang; Ge Yu; Ping Zhao; Xing Chen; Jian Liu; Xiaodong Liu; Shaowu Wang; Zhongshi Zhang; Yongqiang Yu; Yuefeng Li; Liya Jin; Ying Xu; et al. (Advances in Atmospheric Sciences, 2015)

Trace levels of mitomycin C disrupt genomic integrity and lead to DNA damage response defect in long-term-cultured human embryonic stem cells - Di Zhou; Ge Lin; Si-Cong Zeng; Bo Xiong; Ping-Yuan Xie; De-Hua Cheng; Qing Zheng; Qi Ouyang; Xiao-Ying Zhou; Wei-Ling Tang; Yi Sun; Guang-Ying Lu; et al. (Archives of Toxicology, 2015)

Epidemiological situation and genetic analysis of H7N9 influenza viruses in Shanghai in 2013 - Fei-Fei Ge; Hou-Bin Ju; De-Quan Yang; Jian Liu; Jian Wang; Jun Lu; Xin Li; Wei-Yi Zhang; Pei-Hong Liu; Jin-Ping Zhou (Archives of Virology, 2014)

Association between CLPTM1L polymorphisms (rs402710 and rs401681) and lung cancer susceptibility: evidence from 27 case–control studies - De-ping Zhao; Chen-lu Yang; Xiao Zhou; Jia-an Ding; Ge-ning Jiang (Molecular Genetics and Genomics, 2014)

Analyses of the Similarity and Difference of Global Gene Expression Profiles in Cortex Regions of Three Neurodegenerative Diseases: Sporadic Creutzfeldt-Jakob Disease (sCJD), Fatal Familial Insomnia (FFI), and Alzheimer’s Disease (AD) - Chan Tian; Di Liu; Wei Xiang; Hans A. Kretzschmar; Qing-Lan Sun; Chen Gao; Yin Xu; Hui Wang; Xue-Yu Fan; Ge Meng; Wei Li; Xiao-Ping Dong (Molecular Neurobiology, 2014)

Remarkable reductions of PAKs in the brain tissues of scrapie-infected rodent possibly linked closely with neuron loss - Ge Meng; Chan Tian; Hui Wang; Yin Xu; Bao-Yun Zhang; Qi Shi; Chen Gao; Cao Chen; Xue-Yu Fan; Jing Wang; Kang Xiao; Ke Ren; et al. (Medical Microbiology and Immunology, 2014)

Phenotypic characterization of craniofacial bone marrow stromal cells: unique properties of enhanced osteogenesis, cell recruitment, autophagy, and apoptosis resistance - Weijie Dong; Jie Ge; Ping Zhang; Yu Fu; Ziwen Zhang; Jie Cheng; Hongbing Jiang (Cell and Tissue Research, 2014)

Whole-genome analysis of porcine epidemic diarrhea virus (PEDV) from eastern China - De-Quan Yang; Fei-Fei Ge; Hou-Bin Ju; Jian Wang; Jian Liu; Kun Ning; Pei-Hong Liu; Jin-Ping Zhou; Quan-Yun Sun (Archives of Virology, 2014)

Improved zinc tolerance of tobacco by transgenic expression of an allene oxide synthase gene from hexaploid wheat - Huai-Hua Liu; Yuan-Ge Wang; Shu-Ping Wang; Hong-Jie Li; Qing-Guo Xin (Acta Physiologiae Plantarum, 2014)

Development of an ATI-NDVI method for estimation of soil moisture from MODIS data - Lei Lu; Ge-Ping Luo; Ji-Yan Wang (International Journal of Remote Sensing, 2014)

Exposure to diethylhexyl phthalate (DEHP) results in a heritable modification of imprint genes DNA methylation in mouse oocytes - Lan Li; Teng Zhang; Xun-Si Qin; Wei Ge; Hua-Gang Ma; Li-Lan Sun; Zhu-Mei Hou; Hong Chen; Ping Chen; Guo-Qing Qin; Wei Shen; Xi-Feng Zhang (Molecular Biology Reports, 2014)

Organic carbon mineralization responses to temperature increases in subtropical paddy soils - Ping Zhou; Yong Li; Xiu’e Ren; He’ai Xiao; Chengli Tong; Tida Ge; Philip C. Brookes; Jianlin Shen; Jinshui Wu (Journal of Soils and Sediments, 2014)

New cycloartane triterpene glycosides from Beesia calthaefolia - Hong-Jie Li; Li-Hua Mu; Xian-Zhe Dong; Xiao-Yue Ge; Ping Liu (Natural Product Research, 2013)

Epidemiological survey of porcine epidemic diarrhea virus in swine farms in Shanghai, China - Fei-Fei Ge; De-Quan Yang; Hou-Bin Ju; Jian Wang; Jian Liu; Pei-Hong Liu; Jin-Ping Zhou (Archives of Virology, 2013)

Chitosan-functionalized silk fibroin 3D scaffold for keratocyte culture - Linan Guan; Pei Tian; Hongyan Ge; Xianling Tang; Hong Zhang; Lingling Du; Ping Liu (Journal of Molecular Histology, 2013)

Stereoselective syntheses of functionalized spirocyclopenteneoxindoles via triphenylphosphine-catalyzed [3+2] cycloaddition reactions - Qing-Fa Zhou; Xue-Ping Chu; Fei-Fei Ge; Cheng Li; Tao Lu (Molecular Diversity, 2013)

Factors underlying the association of body mass index with serum ALT in Chinese hypertensive adults without known hepatic diseases - Yan Zhang; Xian-hui Qin; Jian-ping Li; Yi-min Cui; Ze-yuan Liu; Zhi-gang Zhao; Jun-bo Ge; De-ming Guan; Jian Hu; Yan-ni Wang; Fu-min Zhang; Xin Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Dynamic analysis for gene expression profiles of endothelial colony forming cells under hypoxia - De-Cai Yu; Wen-Du Feng; Xian-Biao Shi; Zhi-Yong Wang; Wei Ge; Chun-Ping Jiang; Xi-Tai Sun; Yi-Tao Ding (Genes & Genomics, 2013)

Inhibitory effect of curcumin analogs on tissue factor procoagulant activity and their preliminary structure–activity relationships - Hai-Xia Ge; Ling Chen; Jian Zhang; Jun-Ping Kou; Bo-Yang Yu (Medicinal Chemistry Research, 2013)

Effect of land use on the abundance and diversity of autotrophic bacteria as measured by ribulose-1,5-biphosphate carboxylase/oxygenase (RubisCO) large subunit gene abundance in soils - Hongzhao Yuan; Tida Ge; Shenying Zou; Xiaohong Wu; Shoulong Liu; Ping Zhou; Xiaojuan Chen; Phil Brookes; Jinshui Wu (Biology and Fertility of Soils, 2013)

Soil microbial biomass and bacterial and fungal community structures responses to long-term fertilization in paddy soils - Hongzhao Yuan; Tida Ge; Ping Zhou; Shoulong Liu; Paula Roberts; Hanhua Zhu; Ziying Zou; Chengli Tong; Jinshui Wu (Journal of Soils and Sediments, 2013)

Time lag between carbon dioxide influx to and efflux from bare saline-alkali soil detected by the explicit partitioning and reconciling of soil CO2 flux - Xi Chen; Wen-Feng Wang; Ge-Ping Luo; Long-Hui Li; Yan Li (Stochastic Environmental Research and Risk Assessment, 2013)

Molecular epidemiology of hepatitis C virus among different groups of people in the province of Fujian, China - Ying Ye; Yan-sheng Yan; Ge Chen; Ping-ping Yan; Wu-xiong Zheng; Yan-qin Deng; Xiu-hui Yang; Shou-li Wu; Zhi-shan Zhang (Archives of Virology, 2013)

Effects of drought stress on phosphorus and potassium uptake dynamics in summer maize (Zea mays) throughout the growth cycle - Ti-Da Ge; Ning-Bo Sun; Li-Ping Bai; Chen-Li Tong; Fang-Gong Sui (Acta Physiologiae Plantarum, 2012)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

Genome-wide Identification and Characterization of a Dehydrin Gene Family in Poplar (Populus trichocarpa) - Chang-Cai Liu; Chun-Ming Li; Bao-Guang Liu; Su-Jie Ge; Xiu-Mei Dong; Wei Li; Hang-Yong Zhu; Bai-Chen Wang; Chuan-Ping Yang (Plant Molecular Biology Reporter, 2012)

Epidemiological survey and genetic evolution of H9 subtype influenza viruses in Shanghai, China, from 2006 to 2010 - Jin-Ping Zhou; Fei-Fei Ge; Jian Liu; Hou-Bing Ju; De-Quan Yang; Jian Wang; Wei-Yi Zhang; Pei-Hong Liu (Archives of Virology, 2012)

Overexpressed mutant optineurin(E50K) induces retinal ganglion cells apoptosis via the mitochondrial pathway - Qingfeng Meng; Jia Lv; Hongyan Ge; Lu Zhang; Fei Xue; Yuanmao Zhu; Ping Liu (Molecular Biology Reports, 2012)

Effect of high dietary carbohydrate on growth, serum physiological response, and hepatic heat shock cognate protein 70 expression of the top-mouth culter Erythroculter ilishaeformis Bleeker - Bo Liu; Jun Xie; Xian-ping Ge; Ling-hong Miao; Guangyu Wang (Fisheries Science, 2012)

In Vitro Evaluation of Phospholipase, Proteinase, and Esterase Activities of Candida parapsilosis and Candida metapsilosis - Yi Ping Ge; Gui Xia Lu; Yong Nian Shen; Wei Da Liu (Mycopathologia, 2011)

Infrasound Exposure Induces Apoptosis of Rat Cardiac Myocytes by Regulating the Expression of Apoptosis-Related Proteins - Zhao-Hui Pei; Bao-Ying Chen; Ru Tie; Hai-Feng Zhang; Ge Zhao; Ping Qu; Xiao-Xing Zhu; Miao-Zhang Zhu; Jun Yu (Cardiovascular Toxicology, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

East Asian-North Indian Ocean thermal contrast and variation in the East Asian summer monsoon for the past 2650 years - Ge Liu; Ping Zhao; XiuJi Zhou (Science China Earth Sciences, 2011)

Expression and identification of a thermostable malate dehydrogenase from multicellular prokaryote Streptomyces avermitilis MA-4680 - Zong-Da Wang; Bao-Juan Wang; Ya-Dong Ge; Wei Pan; Jie Wang; Lei Xu; Ai-Min Liu; Guo-Ping Zhu (Molecular Biology Reports, 2011)

A 150-year reconstructed summer Asian–Pacific Oscillation index and its association with precipitation over eastern China - Ge Liu; Ping Zhao; Junming Chen (Theoretical and Applied Climatology, 2011)

Probability assessment of river blocking by debris flow associated with the Wenchuan Earthquake - Jian-Qi Zhuang; Peng Cui; Yong-Gang Ge; Yi-Ping He; Ying-Hui Liu; Xiao-Jun Guo (International Journal of Remote Sensing, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Microbial community analysis in crab ponds by denaturing gradient gel electrophoresis - Yan Fen Cheng; Qun Lan Zhou; Jun Xie; Xian Ping Ge; Wei-Yun Zhu; Bo Liu (World Journal of Microbiology and Biotechnology, 2010)

Sanchi ginseng (Panax notoginseng (Burkill) F. H. Chen) in China: distribution, cultivation and variations - Hong Bo Guo; Xiu Ming Cui; Na An; Ge Ping Cai (Genetic Resources and Crop Evolution, 2010)

Effect of needle damage on the release rate of Masson pine (Pinus massoniana) volatiles - Jian-Wei Su; Ju-Ping Zeng; Xiao-Wei Qin; Feng Ge (Journal of Plant Research, 2009)

Distribution, sources, and potential risk of polycyclic aromatic hydrocarbons (PAHs) in drinking water resources from Henan Province in middle of China - Ying-ge Ma; Jin-ping Cheng; Fei Jiao; Ke-xin Duo; Zheng Rong; Ming Li; Wen-hua Wang (Environmental Monitoring and Assessment, 2008)

Overexpression of the trehalose-6-phosphate phosphatase gene OsTPP1 confers stress tolerance in rice and results in the activation of stress responsive genes - Liang-Fa Ge; Dai-Yin Chao; Min Shi; Mei-Zhen Zhu; Ji-Ping Gao; Hong-Xuan Lin (Planta, 2008)

Autophagy is activated and might protect neurons from degeneration after traumatic brain injury - Yan-Bo Zhang; Sheng-Xing Li; Xi-Ping Chen; Li Yang; Yun-Ge Zhang; Ran Liu; Lu-Yang Tao (Neuroscience Bulletin, 2008)

A preliminary study on population genetic structure and phylogeography of the wild and cultivated Zizania latifolia (Poaceae) based on Adh1a sequences - Xin-wei Xu; Wei-dong Ke; Xiao-ping Yu; Jun Wen; Song Ge (Theoretical and Applied Genetics, 2008)

Induction and origin of adventitious shoots from chimeras of Brassica juncea and Brassica oleracea - Xue-Yun Zhu; Man Zhao; Sheng Ma; Ya-Ming Ge; Ming-Fang Zhang; Li-Ping Chen (Plant Cell Reports, 2007)

Fermentation of pretreated sugarcane bagasse hemicellulose hydrolysate to ethanol by Pachysolen tannophilus - Ke-Ke Cheng; Jing-Ping Ge; Jian-An Zhang; Hong-Zhi Ling; Yu-Jie Zhou; Ming-De Yang; Jing-Ming Xu (Biotechnology Letters, 2007)

Artificial synthesis of interspecific chimeras between tuber mustard (Brassica juncea) and cabbage (Brassica oleracea) and cytological analysis - Li-Ping Chen; Ya-Ming Ge; Xue-Yun Zhu (Plant Cell Reports, 2006)

A clinical and molecular-genetic analysis of Chinese patients with lattice corneal dystrophy and novel Thr538Pro mutation in theTGFBI (BIGH3) gene - Ping Yu; Yangshun Gu; Yuehong Yang; Xiaoyi Yan; Liu Chen; Zhen Ge; Ming Qi; Jianmin Si; Lei Guo (Journal of Genetics, 2006)

Effect of brassinolide on callus growth and regeneration in Spartina patens (Poaceae) - Zhou Lu; Min Huang; Dong-Ping Ge; Yong-Hua Yang; Xiao-Ning Cai; Pei Qin; Jian-Ming She (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)

Research on system of flood disaster control and reduction supported by gis in medium and small basins - You-peng Xu; Jin-kang Du; Li-feng Zhang; Xiao-ping Ge; Bu-zhu Peng (Chinese Geographical Science, 2002)